Spin - Giles, Lamar. 1979- (Scholastic Press, 2019)
When DJ ParSec (Paris Secord), rising star of the local music scene, is found dead over her turntables, the two girls who found her, Kya (her pre-fame best friend) and Fuse (her current chief groupie) are torn between grief for Paris and hatred for each other--but when the lack of obvious suspects stalls the investigation, and the police seem to lose interest, despite pressure from social media and ParSec's loyal fans, the two girls unite, determined to find out who murdered their friend.